Effect of three doses of effective microorganisms applied at two phenological stages of wheat (Triticum sp.), Santa Rosa variety. Macashca rural center, Huaraz, Ancash, 2023 (Aporte Santiaguino, 2025)
The research was conducted in the rural center of Macashca, located in the district of Huaraz, Huaraz province, Ancash region, with the objective of evaluating the effect of three doses of effective microorganisms (EM) at two phenological stages of the wheat crop (Triticum sp.), Santa Rosa variety. A Completely Randomized Block Design (CRBD) with a 4 x 2 factorial arrangement and 4 blocks was used, applying EM to the wheat crop population and sampling one linear meter of wheat. The variables studied were plant height, spike length, number of grains per spike, grain weight per spike, yield, and profitability. The best results for microorganism doses were observed with D3 (5% EM dose) in terms of yield, while the phenological stages EFV and EFR showed the most significant effects on the variables. Treatment T4 achieved the most notable results, with a plant height of 139.05 cm, grain weight per spike of 3.36 g, yield of 2146.43 kg/ha, profitability of 76.29%, and net profit of S/ 3,715.46. Treatment T8 stood out for spike length (10.38 cm) and the number of grains per spike (50.38 units).
Keywords: Effective Microorganisms; Phenological Stage; Wheat